The Use of Video in Improving Students’ Attention in Learning Process of Kindergarten Students - Sihotang, Romaida Annamaria; Cendana, Wiputra; Kristidhika, Dita Ciptaningtyas (International Journal of Elementary Education, 2020)
One problem that often arises in the learning process is that students' attention is quite minimal during the learning process. This thing cannot be separated from the characteristic of kindergarten students, that is they have a short attention span. This, of course, can make the learning process ineffective. It is important to use the teacher's creativity to make the students pay attention during the learning process. Teachers can take advantage of the current industrial revolution 4.0 by using the technologies around them, such as the use of videos to attract students' attention so that the learning process becomes effective. This paper aims to see the effectiveness of the use of video to attract students' attention. Education is a learning process that occurs throughout life. Student’s attention is needed for the material taught by the teacher during the learning process. It will make the students able to understand the material being taught. The use of video is very effective in attracting the students’ attention. It is necessary for the teacher to know the characteristics of the students and to follow the development of technology to be able to provide the teaching media that suits the students' needs.